PI3K-C2γ is a Rab5 effector selectively controlling endosomal Akt2 activation downstream of insulin signalling - Braccini, L.; Ciraolo, E.; Campa, C.; Perino, A.; Longo, D.; Tibolla, G.; Pregnolato, M.; Cao, Y.; Tassone, B.; Damilano, F.; Laffargue, M.; Calautti, E.; et al. (Nature Publishing Group, 2015)
In the liver, insulin-mediated activation of the phosphatidylinositol 3-kinase (PI3K)/Akt pathway is at the core of metabolic control. Multiple PI3K and Akt isoenzymes are found in hepatocytes and whether isoform-selective interplays exist is currently unclear. Here we report that insulin signalling triggers the association of the liver-specific class II PI3K isoform γ (PI3K-C2γ) with Rab5-GTP, and its recruitment to Rab5-positive early endosomes. In these vesicles, PI3K-C2γ produces a phosphatidylinositol-3,4-bisphosphate pool specifically required for delayed and sustained endosomal Akt2 stimulation. Accordingly, loss of PI3K-C2γ does not affect insulin-dependent Akt1 activation as well as S6K and FoxO1-3 phosphorylation, but selectively reduces Akt2 activation, which specifically inhibits glycogen synthase activity. As a consequence, PI3K-C2γ-deficient mice display severely reduced liver accumulation of glycogen and develop hyperlipidemia, adiposity as well as insulin resistance with age or after consumption of a high-fat diet. Our data indicate PI3K-C2γ supports an isoenzyme-specific forking of insulin-mediated signal transduction to an endosomal pool of Akt2, required for glucose homeostasis.